2013
DOI: 10.1017/thg.2013.15
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Wall Thickness and Amniotic Fluid Albuminuria in Growth-Restricted Twin Fetuses

Abstract: Background and objective: Intrauterine growth restriction (IUGR) may be associated with significantly higher aortic intima-media thickening (aIMT) values. It is unknown if fetal aIMT is associated with glomerulosclerosis and amniotic albuminuria in utero. Design, setting, participants, and measurements: Fetal abdominal aIMT and amniotic albumin/creatinine ratio (ACR) were measured in 126 individual twin fetuses, recruited by the Obstetrics and Gynaecology Clinics of the University of Padua (Italy) Medical Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Although many cases lack an identifiable cause, FGR is strongly associated with fetal demise, and accompanies 50% of unexplained stillbirths (2). Positive correlations between low birth weight, increased risk of adult cardiovascular disease and stroke have been documented, with growing evidence of the latent consequences of adverse prenatal programming (3,4).…”
mentioning
confidence: 99%
“…Although many cases lack an identifiable cause, FGR is strongly associated with fetal demise, and accompanies 50% of unexplained stillbirths (2). Positive correlations between low birth weight, increased risk of adult cardiovascular disease and stroke have been documented, with growing evidence of the latent consequences of adverse prenatal programming (3,4).…”
mentioning
confidence: 99%
“…A comparable study in fetal sheep show similar changes in the biomechanical properties of the aorta from FGR, however, those changes were not paralleled by modifications in the vessel morphology and no data regarding the vasocontractile response is provided (Dodson et al, 2014). Compelling evidence in humans show that FGR is associated with an increased aortic intima-media thickness and decreased internal diameter (Skilton et al, 2005; Koklu et al, 2007; Visentin et al, 2013; Zanardo et al, 2013; Stergiotou et al, 2015) which can be evidenced even in utero (Cosmi et al, 2009; Gomez-Roig et al, 2015). Interestingly, the increase in aortic intima-media thickness in human FGR is associated with an increase in the umbilical artery pulsatility index (Cruz-Lemini et al, 2014) an effect also observed in this model (Herrera et al, 2016).…”
Section: Discussionmentioning
confidence: 99%